2017
DOI: 10.1016/j.apmr.2016.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Functional Goals and Predictors of Their Attainment in Low-Income Community-Dwelling Older Adults

Abstract: Objective To describe functional goals and factors associated with goal attainment among low-income older adults with disabilities living in the community. Design Secondary analysis from two studies of CAPABLE. Functional goals were coded using the International Classification of Functioning, Disability, and Health (ICF) framework. The percentage of goals attained at five months follow-up was computed within each ICF domain. Multivariate logistic regression was used to identify factors associated with goal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Goals in the physical cluster were the most likely to be attained and goals in the pain and mobility clusters seemed the most difficult to attain. Again, Waldersen et al also found that goals related to mobility (walking) and pain (within body functions) had the lowest attainability [37]. There is little evidence explaining the difference in goal attainability across clusters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Goals in the physical cluster were the most likely to be attained and goals in the pain and mobility clusters seemed the most difficult to attain. Again, Waldersen et al also found that goals related to mobility (walking) and pain (within body functions) had the lowest attainability [37]. There is little evidence explaining the difference in goal attainability across clusters.…”
Section: Discussionmentioning
confidence: 99%
“…Health is thus an important goal, even when seen in a broader life-goal perspective. Indeed, in the study of Waldersen et al [37] among community-living older adults receiving occupational therapy at home, goals were mainly focused on mobility and the least on self-care. Similar to our results, in this study it was found that 72% of goals were attained.…”
Section: Discussionmentioning
confidence: 99%
“…While not a consideration in the study, personal tenacity and the ability to modify personal goals over time may contribute to increased life satisfaction (Bailly, Gana, Hervé, Joulain, & Alaphilippe, 2014). Using a collaborative goal setting model, Waldersen et al,(2014) found when older adults were flexible and willing to adopt new strategies, opportunity for goal attainment increased.…”
Section: Discussionmentioning
confidence: 99%
“…Expanding upon ABLE, CAPABLE is a 16-week structured program delivered by OTs who conduct six home visits and provide assistive devices, RNs who conduct four home visits, and a handyman who provides home alterations (ie, installs devices, makes environmental modifications, and performs home repair). [15][16][17][18][19] Similar to ABLE, the CAPABLE interdisciplinary team provided consultation with older adults to help them identify daily activity goals (eg, taking a shower and walking to the bathroom), evaluated barriers to achieving those goals, and attained outcomes collaboratively. 11,18 The OT assists older adults to perform ADLs, instrumental ADLs (IADLs), and discretionary activities that are challenging at home, such as functional mobility, meal preparation, bathing, and dressing.…”
Section: Model Descriptionmentioning
confidence: 99%